What does it mean to make a joint decision? Unpacking intra-household decision-making in agriculture - Acosta, Mariola (Wageningen University & Research, 2018)
Presented by Mariola Acosta (Wageningen UR / CCAFS), as part of the Annual Gender Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 25-27 September 2018.